Improving the Prospective Math Teacher's Literacy Skills by Using Digital Images in STEM-Based Instruction - Ruslau, Maria F V.; Nur'Aini, Khumaeroh Dwi; Pratama, Rian Ade (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2024)
The demands of high school education are not only increasingly complex and difficult subject content, students are also required to be able to think critically and reason in solving everyday problems. This mathematical ability is known as mathematical literacy proficiency. This is where the teacher's role as a facilitator who provides stimulus in the form of learning strategies, guidance and assistance when students experience learning difficulties is a key factor. For this reason, students as prospective mathematics teachers need to have good mathematical literacy skills and knowledge and skills to guide students to achieve 21st century abilities and skills. This research was conducted to apply a STEM approach in learning so that students can improve the mathematical literacy skills of students majoring in Mathematics Education as prospective teachers and introduce and equip them with knowledge about STEM. The research was carried out using problems related to the relationship between mathematics and digital images in STEM. Data is collected through tests and assessments of student activities that integrate STEM in solving problems. The research results show that digital images have the potential to help students understand mathematical concepts in various fields, especially computer graphics. Students' literacy skills also increased significantly at the significance level α = 0.05. Students' mathematical literacy proficiency level increased from 90% at maximum level 1 to 90% at minimum level 5